Rigorous Dreaming: Curatorial Practices for Large-Scale Disability Performance - Erlich, Shay; Conn, Sarah (Performance Matters, 2025)
“Rigorous Dreaming” explores emergent curatorial practices for large-scale disability-centred performance. As these curatorial practices grow, so too does the need for intentional critique, whether aesthetic, dramaturgical, or ethical, a need that is often filled by simplistic attempts to define what “good” disability art is. This essay traces emergent curatorial practices that support the flourishing of bold large-scale disability performances on national and international stages.These practices are made tangible through an outline of the curatorial approach that the National Arts Centre’s National Creation Fund is developing to engage with disability creation. Rooted in disability justice and led by a collaborative team, this approach centres disability knowledge–generating practices and offers imaginative space for disabled artists to dream about their artistic and production practices. Notably, the approach intentionally centres artistic rigour when considering new artistic creations, rather than relying on specific artistic conventions, using a definition that honours the strategies that are critical for disabled artists when developing their own conventions of rigour. Erlich and Conn argue that it is essential to differentiate between rigour and Western-colonial definitions of professional aesthetics, in order to allow disability-informed definitions of rigour to converge within the discipline.Disabled artists in Canada and beyond deserve creative processes that support them in sharing their stories loudly and boldly in our largest performance forums. Refuting the notion that professional disability art should look a particular way, and celebrating the aesthetic diversity—including the awkward and grotesque—that naturally emerges from rigorous process, “Rigorous Dreaming” champions the curatorial groundwork that is necessary for a supported and thriving disability performance sector in Canada.Plain Language Abstract (adapted by Kelsie Acton with Daniel Foulds)“Rigorous Dreaming” talks about deciding which types of disability art performances get to perform in large theatres. By large theaters, we mean theatres that can fit three hundred people. We are curious about how people decide what shows to put in large theatres. We want to know how people decide if a disability performance is “good” or not. We think that it is important to decide what is “good” by looking at the performance and how the performance is made. We want people to understand what makes disability unique and why disability art might look or be shown differently than most shows in big theatres. This article explains what the people who choose performance and performers need so that they can create disability art for large theatres in Canada and around the world.The writers, Sarah and Shay, both work at the National Arts Centre’s National Creation Fund. This paper talks about how they and other disabled artists are making ways to decide together whether to support a disability performance. This is important because the National Arts Centre is a large theatre that shows many art forms, not just disability art. The ways they have come up with make sure that disability justice, and disability culture, are an important part of making decisions. This includes making sure that artists feel like they have full control to make performances that come from their experiences without worrying about what is “normal” for large theatres. Because of this, we are curious about how and why an artist made the decisions that they did. We think it is important to understand how and why something was created before we make a decision. We also think that how the work looks or is performed should be judged by disabled standards. Disabled artists shouldn’t be judged by what we usually see in large theatres.We want disabled artists in Canada and across the world to be able to make the art that is important to them. We want disabled artists to show their art in the largest theatres in the world. We think that disability art that comes from our own experience and culture is beautiful and professional and should be celebrated. We know that disability can be messy and complicated. Sometimes, our art is messy and complicated too. This is a natural part of disability art, and we want theatres around the world to understand that this is a beautiful and professional part of our work. We hope that this article helps theatres and artists have an easier time talking to each other about how wonderful disability arts can be for everyone.